One-sided approximation of a step by algebraic polynomials in the mean - Motornaya, O. V.; Motornyi, V. P.; Nitiema, P. K. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
An asymptotically sharp estimate is obtained for the best one-sided approximation of a step by algebraic polynomials in the space L_1.